1997
DOI: 10.1007/s100480050008
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the δ-sarcoglycan gene are a rare cause of autosomal recessive limb-girdle muscular dystrophy (LGMD2)

Abstract: The dystrophin-based membrane cytoskeleton of muscle fibers has emerged as a critical multi-protein complex which seems to impart structural integrity on the muscle fiber plasma membrane. Deficiency of dystrophin causes the most common types of muscular dystrophy, Duchenne and Becker muscular dystrophies. Muscular dystrophy patients showing normal dystrophin protein and gene analysis are generally isolated cases with a presumed autosomal recessive inheritance pattern (limb-girdle muscular dystrophy). Recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…The sarcoglycan complex constitutes a transmembrane component of the dystrophin-glycoprotein complex (DGC), which links the cytoskeleton to the extracellular matrix (Wheeler and McNally, 2003). d-Sarcoglycan (d-SG) mutations may lead most frequently to a complete loss or a strong reduction of the whole SG complex (Duggan et al, 1997) and are associated with a form of autosomal recessive limb-girdle muscular dystrophy 2F (LGMD2F). Patients with LGMD2F present progressive weakness, with respiratory failure and dilated cardiomyopathy (Nigro et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The sarcoglycan complex constitutes a transmembrane component of the dystrophin-glycoprotein complex (DGC), which links the cytoskeleton to the extracellular matrix (Wheeler and McNally, 2003). d-Sarcoglycan (d-SG) mutations may lead most frequently to a complete loss or a strong reduction of the whole SG complex (Duggan et al, 1997) and are associated with a form of autosomal recessive limb-girdle muscular dystrophy 2F (LGMD2F). Patients with LGMD2F present progressive weakness, with respiratory failure and dilated cardiomyopathy (Nigro et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The disease is caused by mutations in a number of responsible genes, [13][14][15][16][17] including sarcoglycan genes ␣ (LGMD 2D), ␤ (LGMD 2E), ␥ (LGMD 2C) and ␦ (LGMD 2F), respectively. 14,[18][19][20][21][22][23][24] While the phenotype of the sarcoglycanopathies is variable, patients often show a severe progression, with fatality in the second or third decade.…”
Section: Introductionmentioning
confidence: 99%
“…16,34,35,37,40,42 Loss of any single component of the sarcoglycan complex results in a decrease of the expression of other components, 5,28,30,31 and mutations within this complex are now recognized as a primary cause of four autosomal recessive forms of dystrophy resembling Duchenne and Becker muscular dystrophies. 5,10,11,24,28,30,31,33,36 Although deficiencies in components of the dystrophin cytoskeleton and basal lamina result in pathologic phenotypes, the primary absence of one component often leads to secondary deficiencies of other components. 4,5,31,32 This observation has led to attempts to identify single components that, when deficient, result in muscular dystrophy; however, important case studies have been reported which contradict a single factorial model in muscular dystrophy.…”
mentioning
confidence: 99%